1995
DOI: 10.1145/203241.203253
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the way programmers think about new programming environments

Abstract: An interesting usability study of a prototype development environment for the Dylan programming language is presented here. This study's purpose is to determine just how close the prototype is to developers. New approaches to source code organization and to the relationship between the environment and the application being developed are introduced. An asessment of how effectively the prototype conveys these innovations to Dylan developers is also given, followed by some proposed improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Research on tailoring has explored augmentation and exclusion operations on operating systems (North and Shneiderman, 2000), groupware (Wulf et al, 1999), and coordination systems (Cortes, 2000). In operating system visualization work by North and Shneiderman (2000) and Dumas and Parsons (1995), best views of operating system windows were identified that functionally support user defined modifications. Wulf et al (1999) explored groupware systems and described how a group in the ongoing use of a technology achieves coordinated views.…”
Section: Component Architecturesmentioning
confidence: 99%
“…Research on tailoring has explored augmentation and exclusion operations on operating systems (North and Shneiderman, 2000), groupware (Wulf et al, 1999), and coordination systems (Cortes, 2000). In operating system visualization work by North and Shneiderman (2000) and Dumas and Parsons (1995), best views of operating system windows were identified that functionally support user defined modifications. Wulf et al (1999) explored groupware systems and described how a group in the ongoing use of a technology achieves coordinated views.…”
Section: Component Architecturesmentioning
confidence: 99%
“…The Apple Dylan programming environment [DP95] lets users choose which pairs of views to coordinate. Users browse hierarchical object-oriented programs by splitting and linking frames so that selecting a folder in one frame displays its contents in the other frame (e.g.…”
Section: Coordinationsmentioning
confidence: 99%
“…In the Snap user interface, users coordinate a pair of visualizations by dragging the Snap button from one to the other (similar to [JBO94] and [DP95]). This displays the Snap Specification dialog (Figure 3).…”
Section: No Relationship: If the Schema Has No Relationship Between Tmentioning
confidence: 99%
“…The Apple Dylan programming environment [DP95] lets users split and link frames for drilling down through file structures (similar to Windows Explorer).…”
Section: -Aggregations and Coordinated Displaysmentioning
confidence: 99%